How Does Immigration Status and Citizenship Affect Identity Theft Victimization Risk in the US? Insights from the 2018 National Crime Victimization Survey Identity Theft Supplement - Irvin-Erickson, Yasemin (Victims & offenders, 2023)
There has been no research study to date in the United States (US) looking at how an individual’s immigration status and citizenship might affect their odds of becoming an identity theft victim. This study fills this gap by analyzing the relationship between immigration status and identity theft victimization risk with recently released data from the 2018 iteration of the US National Crime Victimization Survey’s Identity Theft Supplement. Descriptive analysis presents demographics, risky and protective behavior, and identity theft prevalence across US-born citizens, naturalized citizens, non-citizens, and individuals with an ambiguous citizenship status in the US. Logistic regression models explore the differences between these groups in their identity theft victimization risk controlling for other demographic factors and known correlates of identity theft. Results suggest that US-born citizens, naturalized citizens, and non-citizens are at the end of the spectrum with a higher risk of identity theft victimization, whereas individuals with an ambiguous immigration status are at the lower end. Implications of the study findings and future avenues for data collection and research are discussed.